THE IMPACT OF THE 19TH CENTURY EUROPEAN COLONIALISM IN AFRICA, IN THE NOVEL “THINGS FALL APART” BY CHINUA ACHEBE - Afriliyani Piola; Happy Anastasia Usman (British : Jurnal Bahasa dan Sastra Inggris, 2019)
Things Fall Apart is a novel potrays the background of traditional life and primitive culture Ibo tribe in Umuofia, Nigeria, Africa and also the impact of European colonialism towards Africans’ society in the early 19th century. The research applies the qualitative method and it supported by the sociology of literature approach. The primary data are taken from the novel Things Fall Apart by Chinua Achebe. Based on the analysis the researcher conducts, the impact of European colonialism in Africa which not only brings a positive impacts but also negative legacy. There are several points of the impact European colonialism in Africa : existence of christianity, existence of language, establishment regulation and contribution to development.